Manajemen Keuangan Sekolah dalam Pemenuhan Sarana Prasarana Pendidikan: School Financial Management in Fulfilling Educational Facilities and Infrastructure - Hasnida, Hasnida; Astuti, Rini (Thawalib: Jurnal Kependidikan Islam, 2024)
Research to analyze and gain insights into the financial management of Public Middle School 22 Sijunjung, West Sumatra, in meeting the educational infrastructure needs. A qualitative approach using phenomenology was employed. Informants included the school principal, secretary, and treasurer. Data collection involved interviews, participatory observation, and document analysis. Data analysis included data condensation, presentation, and conclusion drawing. This study shows that the financial management of the school to meet educational infrastructure needs encompasses school budgeting, budget allocation, financial recording, and financial accountability. This study highlights the importance of financial management in providing educational facilities and infrastructure by involving internal and external stakeholders in the evaluation, analysis, monitoring, and fulfilling various school needs.